Analysis of the Application of Logical Operations to Cryptographic Transformations of Information Security Means - Madaminov, M. M.; Farhodjonov, A. F. (Indonesian Journal Publisher, 2024)
In the article, the solution to the problem of determining logical operations that ensure cryptographic stability of the transformation of algorithms of cryptographic methods of information security is justified by the criterion of regularity - equal distribution